Coalbed methane accumulation, in-situ stress, and permeability of coal reservoirs in a complex structural region (Fukang area) of the southern Junggar Basin, China - Li, Meng; Li, Mingjie; Pan, Jienan; Gao, Di; Cao, Yunxing (Frontiers in Earth Science, 2023)
The enrichment of coalbed methane (CBM), in-situ stress field, and permeability are three key factors that are decisive to effective CBM exploration. The southern Junggar Basin is the third large CBM basin in China but is also known for the occurrence of complex geological structures. In this study, we take the Fukang area of the southern Junggar Basin as an example, coalbed methane accumulation and permeability, and their geological controls were analyzed based on the determination of geological structures, in-situ stress, gas content, permeability, hydrology and coal properties. The results indicate that gas contents of the Fukang coal reservoirs are controlled by structural framework and burial depth, and high-to-ultra-high thickness of coals has a slightly positive effect on gas contents. Perennial water flow (e.g., the Baiyanghe River) favors gas accumulation by forming a hydraulic stagnant zone in deep reservoirs, but can also draw down gas contents by persistent transportation of dissolved gases to ground surfaces. Widely developed burnt rocks and sufficient groundwater recharge make microbial gases an important gas source in addition to thermogenic gases. The in-situ stress field of the Fukang area (700~1500 m) is dominated by a normal stress regime, characterized by vertical stress > maximum horizontal stress > minor horizontal stress. Stress ratios, including lateral stress coefficient, natural stress ratios, and horizontal principal stress ratio are all included in the stress envelopes of China. Permeability in the Fukang area is prominently partitioned into two distinct groups, one group of low permeability (0.001~0.350 mD) and the other group of high permeability (0.988~16.640 mD). The low group of permeability is significantly formulated by depth-dependent stress variations, and the high group of permeability is controlled by the relatively high structural curvatures in the core parts of synclines and the distance to the syncline core. Meanwhile, coal deformation and varying dip angles intensify the heterogeneity and anisotropy of permeability in the Fukang area. These findings will promote the CBM recovery process in China and improve our understanding of the interaction between geological conditions and reservoir parameters and in complex structural regions.